2017
DOI: 10.1007/s10096-017-3049-x
|View full text |Cite
|
Sign up to set email alerts
|

The recomBead Borrelia antibody index, CXCL13 and total IgM index for laboratory diagnosis of Lyme neuroborreliosis in children

Abstract: For laboratory diagnostics of Lyme neuroborreliosis (LNB), the recomBead Borrelia antibody index (AI) assay has shown promising results in a mixed age population, but has not previously been evaluated with specific focus on paediatric patients. The aim of the study was to evaluate the recomBead Borrelia AI assay in cerebrospinal fluid (CSF) for the laboratory diagnosis of LNB in children. We also wanted to explore whether early markers, such as CXCL13 in CSF and/or total IgM index could be useful as complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
4
16
1
Order By: Relevance
“…However, most studies measuring CXCL13 using ELISA and lateral flow (LFA) methods have shown elevated CXCL13 circulation levels in the CSF of patients with acute neuroborreliosis compared to other tested groups. Results of the available studies suggest its very high diagnostic value and report its high sensitivity and specificity [5][6][7][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. These studies are in agreement with a meta-analysis performed by Yang J. et al, who confirmed that CXCL13 has a high sensitivity and specificity for diagnosing neuroborreliosis [68].…”
Section: Cxcl13 Concentrationsupporting
confidence: 85%
See 3 more Smart Citations
“…However, most studies measuring CXCL13 using ELISA and lateral flow (LFA) methods have shown elevated CXCL13 circulation levels in the CSF of patients with acute neuroborreliosis compared to other tested groups. Results of the available studies suggest its very high diagnostic value and report its high sensitivity and specificity [5][6][7][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. These studies are in agreement with a meta-analysis performed by Yang J. et al, who confirmed that CXCL13 has a high sensitivity and specificity for diagnosing neuroborreliosis [68].…”
Section: Cxcl13 Concentrationsupporting
confidence: 85%
“…The aims of pediatric studies included a reduction in mortality rates and control of the spread of infectious diseases. These studies have proven that CXCL13 concentration in the CSF of pediatric patients is significantly increased in neuroborreliosis compared to non-neuroborreliosis individuals [8,9,44,47]. One study revealed that differences in CXCL13 levels between children with neuroborreliosis and those with other conditions were statistically significant, although relatively small [45].…”
Section: Cxcl13 In Pediatric Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated in many inflammatory states, it appears to be disproportionately elevated in patients with LNB. 34,35 As such, it has been proposed as an adjunctive diagnostic marker. Although its specificity remains to be determined, 36 it does appear to decrease rapidly with effective treatment, making it a potential marker of treatment efficacy.…”
Section: Confirmatory Testingmentioning
confidence: 99%